Gendered Perceptions of Batterer Intervention Co-Facilitation - Boston, Dorothy Lynne (2010)
The purpose of this dissertation was to examine the experience of co-facilitating male batterer intervention groups as reported by male and female facilitators and to identify how that experience differs along gender lines, given that dual-gender facilitation is an expectation of licensing standards that has not been researched. The following research questions were asked: 1) are there notable differences in how co-facilitation of male batterer intervention groups is experienced by males and females, 2) are females more sensitive to and affected by issues of power and control within the facilitation process than their male peers, and 3) is it more challenging for females to maintain a position of authority within the group process than it is for their male peers? Semi-structured interviews were completed with eleven co-facilitators of licensed batterer intervention groups, and data was compiled regarding their reported experiences. Results indicate that male and female facilitators identify success in similar ways and maintain motivation for this line of work in similar ways. Males and females both reported heightened awareness of power and control issues in relationships and interactions, but for female facilitators this reflected an increased awareness of female power and control strategies. Males and females both value dual-gender co-facilitation, and both are targets of attempts at collusion, but males are more likely to be approached with camaraderie by group members whereas females are more likely to be approached with compliments or attempts at flirtation. Contrary to expectations, power and control issues between male and female co-facilitators did not arise as an issue. Female facilitators were found to maintain authority within the group process. The main finding of this study is that dual-gender facilitation represents a best practice in batterer intervention from the perspective of facilitators